Resveratrol Dose-Dependently Protects the Antioxidant Mechanism of Hydrogen Peroxide-Exposed Healthy Cells and Lung Cancer Cells - Öznur Yurdakul; Aysun Özkan (European Journal of Biology)
Objective: The objective of this study was to investigate the protective effects and the underlying mechanisms of resveratrol against hydrogen peroxide (H2O2 )-induced oxidative stress in healthy human and lung cancer cells. Materials and Methods: The cytotoxic doses and IC50 values of resveratrol and hydrogen peroxide for cells were determined by the Cell Titer Blue-Viability Assay kit. The amount of malondialdehyde (MDA) was determined by fluorescence spectrophotometer. The amount of intracellular reduced glutathione level and antioxidant enzyme activities were analyzed by spectrophotometric methods. Results: In both cells, H2O2 treatment alone (IC50 and IC50) increased MDA, glutathione reductase, glutathione S-transferase, selenium-dependent glutathione peroxidase and non-selenium-dependent glutathione peroxidase activities, but glutathione levels decreased compared to the H2O + 2 resveratrol treatment. In addition, high doses of resveratrol alone (IC50 and IC70) induced more oxidative stress in cancer cells than in healthy cells. High doses of resveratrol alone (IC50 and IC70) also showed cytotoxic effects in cells and decreased cell viability. Resveratrol caused more cytotoxic effects in cancer cells compared to healthy cells. Conclusion: The results of this study show that the increase in MDA level and antioxidant enzyme activity caused by highdose resveratrol treatment reveals the prooxidant effect of resveratrol. Our results also showed an antioxidant effect by reducing oxidative stress in cells pre-incubated with low-dose resveratrol and then exposed to H2O2 . Resveratrol has a dose-dependent biphasic (pro/antioxidant) effect on the antioxidant mechanism of cells. However, more research is needed to confirm this